The police and excessive use of force - Wolny, Philip (Understanding the Black Lives Matter movement., 2021)
Explores the Black Lives Matter movement which protests excessive use of force by police departments against persons of color. Highlights high-profile cases and documents both law enforcement and Black Lives Matter responses. Includes color photographs, sidebars, a glossary, and additional resources.